Effectiveness of Dick & Carey Instructional Design Model and Learning Attitudes Towards Science Learning Outcomes at UPT SMPN 2 Bayang - Kiki Permatasari; Darmansyah; Zulhendri Zen; Ridwan (Jurnal Penelitian Pendidikan IPA, 2025)
Learning outcomes are important for students. In the implementation of learning in schools, efforts to improve student learning outcomes experience many obstacles and barriers. This study aims to test the effect of the Dick & Carey instructional design model and learning attitudes on students' science learning outcomes. This instructional design model is expected to improve students' science learning outcomes compared to the TPACK instructional design model. The type of research used is a quasi-experiment with a Treatment by Block design. This study involved 2 classes, the experimental class, namely the class that was given treatment with the application of the Dick & Carey instructional design model, while the control class was the class that used the TPACK instructional design model. The results of the data analysis showed that students who were taught with the Dick & Carey instructional design model, both those with good or bad attitudes, obtained significantly higher learning outcomes than the science learning outcomes of students taught with the TPACK instructional design model. And there is the effectiveness of the application of the Dick & Carey instructional design model and learning attitudes towards student learning outcomes. In general, learning with the Dick & Carey instructional design model is more effective than learning with the TPACK instructional design model.